2003
DOI: 10.1189/jlb.0203054
|View full text |Cite
|
Sign up to set email alerts
|

RhoA activation promotes transendothelial migration of monocytes via ROCK

Abstract: Monocyte infiltration into inflamed tissue requires the initial arrest of the cells on the endothelium followed by firm adhesion and their subsequent migration. Migration of monocytes and other leukocytes is believed to involve a coordinated remodeling of the actin cytoskeleton. The small GTPases RhoA, Rac1, and Cdc42 are critical regulators of actin reorganization. In this study, we have investigated the role of Rho-like GTPases RhoA, Rac1, and Cdc42 in the adhesion and migration of monocytes across brain end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 25 publications
3
73
0
3
Order By: Relevance
“…2G). Consistent with previous knowledge on the positive role of RHOA in leukocyte adhesion to endothelium (Francis et al, 2006;Giagulli et al, 2004;Honing et al, 2004;Xu et al, 2010), we observed that enhanced adhesion of FAM65B-deficienct neutrophils to endothelial cells under flow (Fig. 2H).…”
Section: Resultssupporting
confidence: 81%
“…2G). Consistent with previous knowledge on the positive role of RHOA in leukocyte adhesion to endothelium (Francis et al, 2006;Giagulli et al, 2004;Honing et al, 2004;Xu et al, 2010), we observed that enhanced adhesion of FAM65B-deficienct neutrophils to endothelial cells under flow (Fig. 2H).…”
Section: Resultssupporting
confidence: 81%
“…According to Carman et al, endothelial membranes positive for caveolin-1 are associated with the transmigrating leukocyte in the transmigration cup, which is dependent on the presence of lipid rafts and their recruitment of CAMs [74,100]. In this context, lipid rafts are believed to coordinate outside-in signaling in ECs and regulation of actin remodeling by lipid raft-associated small guanosine triphosphatases, such as Rho [104][105][106] and Rac [107,108], myosin-dependent contractions [109], and junctional protein regulation [8,110]. These transendothelial migration events are highly organized around CAMmediated signaling within lipid raft structures and support the concept of functionally distinct endothelial adhesion rafts.…”
Section: Adhesion Raftsmentioning
confidence: 99%
“…42,43 The Rho GTPases Rac, Cdc42, and Rho play an important role in the regulation of actin organization in cell motility and movement. In microglia, MCP-1 rapidly induced the activation of Rac, Cdc42, and Rho proteins, which were inhibited by LJ529 (Figure 4, A-C).…”
Section: Lj529 Disturbs Mcp-1-induced Spatial Localization Of Rho Gtpmentioning
confidence: 99%